1999
DOI: 10.1099/00221287-145-10-2931
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of polyphosphate kinase gene expression in Acinetobacter baumannii 252

Abstract: A strain of Acinetobacter baumannii cultured in butyric acid media was found to take up phosphate following a period of phosphate release. PCR was used to clone the polyphosphate kinase (ppk) gene from the strain. The promoter for the ppk gene was functional in the heterologous Escherichia coli host. Using RT-PCR, transcription of the ppk gene was found to be regulated by phosphate concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
(13 reference statements)
1
8
1
4
Order By: Relevance
“…In contrast, neither carbon nor nitrogen limitation led to the triggering of ppk expression (data not shown). These results indicate that the expression of ppk in S. lividans TK24 is triggered when P i becomes limiting in the growth medium, as previously demonstrated in other bacteria (8,9).…”
Section: Resultssupporting
confidence: 70%
“…In contrast, neither carbon nor nitrogen limitation led to the triggering of ppk expression (data not shown). These results indicate that the expression of ppk in S. lividans TK24 is triggered when P i becomes limiting in the growth medium, as previously demonstrated in other bacteria (8,9).…”
Section: Resultssupporting
confidence: 70%
“…When compared to the control cells at the end of the starvation phase (T4) the expression of ppk1 was 4.2-fold lower in the treated cells, rising to 3.7-fold higher at after overplus (T6). Upregulation of ppk1 expression would therefore appear to begin after the addition of Pi to Pi-starved M. mazei cells and thus differ from the majority of previous bacterial overplus studies where ppk (and ppx) expression has been shown to begin during the Pi starvation phase, under the control of the PHO regulon [57][58][59][60][61][62][63] .…”
Section: Discussioncontrasting
confidence: 76%
“…Their expression patterns suggest they are involved in both the formation and degradation processes in Accumulibacter, although the exact factor(s) triggering their induction in the two phases are not clear. It was suggested that ppk1 was under Pho regulon control in Klebsiella aerogenes (Kato et al, 1993) and Acinetobacter baumannii (Gavigan et al, 1999), with transcription being induced by P i limitation. If control mechanisms were similar in Accumulibacter, ppk1 transcript abundance would be expected to increase in the P i -depleted aerobic famine phase.…”
Section: Discussionmentioning
confidence: 99%